ANALISIS PENENTUAN KEPENTINGAN JALAN POROS KABUPATEN ANTAR KECAMATAN DI KABUPATEN TRENGGALEK UNTUK MENDUKUNG PENGEMBANGAN WILAYAH - Catur Widiasmoro; Hitapriya Suprayitno; Eko Budi Santoso (Institut Teknologi Sepuluh Nopember, 2018)
Infrastructure has a very important role as certain to instigates economic growth and regional development. Transportation serves facility for production and investment systems that enables regional services and activities. Region developed on potential itself, to support it how determines best alternative of road links is required. To obtain weight of criteria in this research using pairwise comparison, and furthermore the Technique for Order Preference by Similarity to Ideal Solution is used to discover preference value from each road links. This research indicates that preference inter-districts road Bendo-Surodakan is the main priority with value of preference 3,07, then Suruh-Pule, Gandusari-Kampak road link with score 2,44 and 2,30, consecutively. Road link with lowest score obtained by Bangunsari-Bulu as 0,057